Association between accounting for biological assets and the cost of debt for the firms in the global economy: impact of the implementation of amended IAS 41 - Moutinho, Rafael Antonio (2022)
This study investigates the effect of amended IAS 41 on the cost of debt of the firms in the global economy that adopt IFRS. This amendment determines that bearer plants should be valued at historical cost. Although prior research documents that the fair value measurement of bearer plants is associated with higher firms\' cost of capital, the impact of amended IAS 41 implementation on the cost of debt was still not examined. To explore this context, I utilize panel data ordinary least square (POLS), fixed-effects, random effects, and GMM dynamic panel data regression models for a sample decomposed in non-bearer (i.e. consumable biological assets) and bearer plants subsamples from 140 companies located in 43 countries from 2005 to 2019. Firstly, my findings are consistent with prior research as it indicates that fair value accounting for biological assets other than the bearer plants subset is associated with lower firms\' cost of debt. This study also evidences that the measurement of bearer plants at fair value is associated with a higher cost of debt from 2005 to 2019 period; however, the historical cost accounting for bearer plants in the post-amended IAS 41 period (2016-2019) did not reduce the cost of debt of firm, suggesting that although the historical cost accounting for bearer plants is associated with firms\' lower cost of debt, the amendments on IAS 41 did not still result in a lower cost of debt for firms that shifted from fair value to historical cost accounting of bearer plants subset. Additionally, the fair value model conveys information on future cash flows that reflects the future economic benefits, and firms that shifted from fair value to historical cost accounting have lost this information content, which might have impacted creditors\' assessment of the cost of debt. I expect that my findings are relevant for regulatory and standard-setters, such as the IASB, to assess the effect of amended IAS 41 and propose accounting policies aimed to improve accounting harmonization in the agricultural sector.